Persepsi Orang Tua Siswa Tentang Proses Pembelajaran Tatap Muka Terbatas di SMP Negeri 4 Luwuk - Afriyani Habibu; Moh. Fahri Haruna; Nurlia Nurlia; Alwia Samaduri (Jurnal Biologi Babasal, 2022)
Abstract: The Covid epidemic is believed to have caused issues with online learning and lowered the standard of education in Indonesia. As a result, the government has started to set up a plan that may be carried out in person. A new policy governing restricted face-to-face learning has been implemented since July 2021. If teachers are immunized, set rigorous health standards in the school setting, and limit instruction hours, the limited face-to-face learning method can be implemented. The purpose of this study is to ascertain how parents see the restricted face-to-face instructions offered at SMP Negeri 4 Luwuk. The type of this research is descriptive qualitative. The population was all parents of 256 students of the school. There were 50 parents become the research sample, who have been selected through the cluster sampling technique. Data collection methods included a questionnaire with ten items and a Likert scale. To determine the parent’s impressions of restricted face-to-face learning, the data were examined using descriptive  statistical techniques. The findings revealed that 26 respondets, or 56% of 50 parents, rated the restricted face-to-face learning procedure as good. The view of parents concerning restricted  face-to-face learning at SMP Negeri 4 Luwuk is then shown to be in a good category.